Cardiac mortality in patients randomised to elective coronary revascularisation plus medical therapy or medical therapy alone: a systematic review and meta-analysis. (18th May 2021) - Navarese, Eliano P; Lansky, Alexandra J; Kereiakes, Dean J; Kubica, Jacek; Gurbel, Paul A; Gorog, Diana A; Valgimigli, Marco; Curzen, Nick; Kandzari, David E; Bonaca, Marc P; Brouwer, Marc; Umińska, Julia; et al.
Abstract: Aims: The value of elective coronary revascularisation plus medical therapy over medical therapy alone in managing stable patients with coronary artery disease is debated. We reviewed all trials comparing the two strategies in this population. Methods and results: From inception through November 2020, MEDLINE, EMBASE, Google Scholar, and other databases were searched for randomised trials comparing revascularisation against medical therapy alone in clinically stable coronary artery disease patients. Treatment effects were measured by rate ratios (RRs) with 95% confidence intervals, using random-effects models. Cardiac mortality was the pre-specified primary endpoint. Spontaneous myocardial infarction (MI) and its association with cardiac mortality were secondary endpoints. Further endpoints included all-cause mortality, any MI, and stroke. Longest follow-up data were abstracted. The study is registered with PROSPERO (CRD42021225598). Twenty-five trials involving 19 806 patients (10 023 randomised to revascularisation plus medical therapy and 9783 to medical therapy alone) were included. Compared with medical therapy alone, revascularisation yielded a lower risk of cardiac death [RR 0.79 (0.67–0.93), P  < 0.01] and spontaneous MI [RR 0.74 (0.64–0.86), P  < 0.01]. By meta-regression, the cardiac death risk reduction after revascularisation, compared with medical therapy alone, was linearly associated with follow-up duration [RR per 4-year follow-up: 0.81 (0.69–0.96), P  = 0.008], spontaneous MI absolute difference ( P  = 0.01) and percentage of multivessel disease at baseline ( P  = 0.004). Trial sequential and sensitivity analyses confirmed the reliability of the cardiac mortality findings. All-cause mortality [0.94 (0.87–1.01), P  = 0.11], any MI ( P  = 0.14), and stroke risk ( P  = 0.30) did not differ significantly between strategies. Conclusion: In stable coronary artery disease patients, randomisation to elective coronary revascularisation plus medical therapy led to reduced cardiac mortality compared with medical therapy alone. The cardiac survival benefit after revascularisation improved with longer follow-up times and was associated with fewer spontaneous MIs. Graphical Abstract: